Perancangan User Experience Aplikasi Informasi Lomba Karya Tulis Ilmiah Mahasiswa Menggunakan Metode Human-Centered Design - Kresna Rizka Carisfian; Agi Putra Kharisma; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Scientific paper is a work created and presented in scientific form on a scientific media. The Information Application for Student Scientific Paper Contest or Berlaga aims to facilitate the search for information scientific paper competitions, facilitate the committee in promoting the competition they hold. User Experience is a perception and response that user achieve from using system or product, this perception and response include emotion, faith, perception choice, physic response, psychological, behavior, and that's achieved by user from before using, using it, and after using it, Human-Centered Design is a method inside the sistem design that have purposes which is, making interactive sistem that focused to the system utilization, human factors application, or even ergonomic aspect that have function to increase efficiency, effectiveness, and user satisfaction. After being tested with usability testing for Berlaga application, the result is 96.5% and categorized as very good or the value is above 80%, the detail is 100% for effectiveness aspect, 100% for efficiency aspect, and 89.75% for satisfaction aspect. For the UEQ test, the value for the scale of attractiveness 2.38, perspicuity 2.46, efficiency 2.25, dependability 2.40, stimulation 2.18, and novelty 2.30, categorized as excellent with 10% best average from interval UEQ benchmarck.